Medicare and Private Spending Trends From 2008 to 2012 Diverge in Texas. (February 2015) - Franzini, Luisa; Taychakhoonavudh, Suthira; Parikh, Rohan; White, Chapin
The recent relatively slow growth in health care spending masks significant differences among payers, clinical settings, and geographic areas. To better understand the spending slowdown, we focus on 2008-2012 trends in Texas among Medicare fee-for-service beneficiaries and enrollees in Blue Cross Blue Shield of Texas (BCBSTX). Spending per person for Medicare grew only 1.5% per year on average, compared with 5.2% for BCBSTX. In Medicare, utilization rates were relatively flat, while prices grew more slowly than input prices. In BCBSTX, spending growth was driven by increases in negotiated prices, in particular hospital prices. We find that geographic variation declined sharply in Medicare, due to drops in spending on post–acute care in two notoriously high-spending regions but rose slightly in BCBSTX. The aggregate spending trends mask two divergent stories: spending growth in Medicare is very slow, but price increases continue to drive unsustainable spending growth among the privately insured.